The Hox gene Abdominal‐B regulates the appendage development during the embryogenesis of scorpionflies. Issue 5 (25th May 2022) - Liu, Bing‐Peng; Ding, Guo; Miao, Ying; Hua, Bao‐Zhen
Abstract: The Homeotic Complex (Hox) genes encode conserved homeodomain transcription factors that specify segment identity and appendage morphology along the antero‐posterior axis in bilaterian animals. The Hox gene Abdominal‐B ( Abd‐B ) is mainly expressed in the posterior segments of the abdomen and plays an important role in insect organogenesis. In Mecoptera, the potential function of this gene remains unclear yet. Here, we performed a de novo transcriptome assembly and identified an Abd‐B ortholog in the scorpionfly Panorpa liui . Quantitative real‐time reverse transcription PCR showed that Abd‐B expression increased gradually in embryos 76 h post oviposition, and was mainly present in the more posterior abdominal segments. Embryonic RNA interference of Abd‐B resulted in a set of abnormalities, including developmental arrest, malformed suckers and misspecification of posterior segment identity. These results suggest that Abd‐B is required for the proper development of the posterior abdomen. Furthermore, in Abd‐B RNAi embryos, the expression of the appendage marker Distal‐less ( Dll ) was up‐regulated and was additionally present on abdominal segments IX and X compared with wild embryos, suggesting that scorpionfly Abd‐B may act to suppress proleg development and has gained the ability to repress Dll expression on the more posterior abdominal segments. This study provides additional information on both the functional and evolutionary roles of Abd‐B across different insects. Abstract : Embryonic knockdown of Abd‐B resulted in a set of abnormalities, including developmental arrest, malformed sucker and misspecification of posterior segment identity in Panorpa liui . Dll expression was normally present in the distal region of all developing appendages in GFP RNAi embryos, but additionally on A9–A10 in Abd‐B RNAi embryos. Abd‐B is required for the proper development of the posterior abdomen during embryogenesis.